Analisis Pengaruh Dimensi Kecemasan Terhadap Sikap Belajar Matematika Siswa Sekolah Dasar - Tri Yanti (CV. Akademi Merdeka, 2026)
This study aims to analyze the effect of anxiety on elementary school students' attitudes in learning mathematics, focusing on two dimensions of anxiety: cognitive and somatic. This study uses a descriptive quantitative approach with a path analysis method based on Partial Least Square (PLS). Data were obtained through a closed questionnaire that had been tested for validity and reliability, and distributed to 50 elementary school students. The results of the analysis showed that cognitive anxiety had a significant effect on students' attitudes (p <0.001), while somatic anxiety did not have a direct effect, but contributed indirectly through cognitive anxiety. These findings indicate that learning interventions that target cognitive aspects are more needed to form positive attitudes towards mathematics. This study contributes to the development of educational strategies that are sensitive to students' psychological aspects, as well as providing practical input for teachers and policy makers in designing emotionally supportive learning environments.